(untitled) - Irving, Washington (New York, NY, 1983)
Washington Irving was America's first internationally acclaimed man of letters. Here in one volume are the writings that established his reputation and earned him the admiration of Hawthorne, Poe, Coleridge, Byron, Scott, and Dickens. Written in the character of an elderly gentleman of the old school, "Letters of Jonathan Oldstyle, Gent." is a series of comic reports on the theater, theater-goers, fashions, balls, courtships, duels, and marriages of his contemporary New York
Keywords: American literature; 19th century